The China longitudinal ageing study: overview of the demographic, psychosocial and cognitive data of the Shanghai sample. (3rd March 2016) - Xiao, Shifu; Lewis, Matthew; Mellor, David; McCabe, Marita; Byrne, Linda; Wang, Tao; Wang, Jinghua; Zhu, Minjue; Cheng, Yan; Yang, Cece; Dong, Shuhui
Abstract: Background : China's ageing population will lead to increased neurodegenerative illness and age-related mental health problems. Aims : The Chinese Longitudinal Ageing Study has been developed to better understand the impact of ageing on cognition and mental health. An overview of the sample, major diagnoses and results of the first wave of data collection is presented. Method : One thousand and sixty-eight elderly Chinese (42.2% male), mean age of 72.8 years (SD = 8.5) completed a comprehensive cognitive, psychosocial and mental health assessment. Results : Mean MMSE score was 24.73 (SD = 6.17). Primary generalised anxiety was detected in 0.4% of the sample. Sub-clinical depression and depressive disorder were diagnosed in 1.7% and 2.4% of the sample, respectively. Most (84.5%) reported subjective memory decline, however 66.5% had no cognitive impairment. Mild Cognitive Impairment (MCI) was detected in 25%, Alzheimer's disease (AD) in 4.7%, vascular dementia in 2.5%, and mixed dementia in 1.3%. Cognition was worse in those 85+ years, but affective disorder rates were not. Conclusion : Higher rates of dementia were detected than previously reported in China. Normative data is presented for common cognitive and mental health assessment and screening tasks in a Chinese population. This suggests that the true incidence of dementia has been underestimated, and requires further investigation.